New echocardiographic techniques in the evaluation of left ventricular function in obesity12. (20th June 2013) - Di Bello, Vitantonio; Fabiani, Iacopo; Conte, Lorenzo; Barletta, Valentina; Delle Donne, Maria Grazia; Cuono, Cucco; Leo, Laura Anna; Dini, Frank Lloyd; Marzilli, Mario; Pinchera, Aldo; Santini, Ferruccio
Abstract Objective: Obesity has reached global epidemic proportions and is associated with numerous comorbidities, including major cardiovascular (CV) diseases. Design and Methods: It has many adverse effects on hemodynamics and CV structure and function: it increases total blood volume and cardiac output, and the cardiac workload is greater. Typically, obese patients have a higher cardiac output but a lower level of total peripheral resistance at any given level of arterial pressure. Most of the increase in cardiac output in obesity is caused by stroke volume, although heart rate typically mildly increases also due to enhanced sympathetic activation. Results: Over the last few years, experimental investigations have unraveled some important pathogenetic mechanisms that may underlie a specific form of "obesity cardiomyopathy." Bariatric surgery represents an effective alternative to treat obesity when nonsurgical weight loss programs (diet + behavior modifications + regular exercise) have failed. A great numbers of questions are still open in the global comprehension of the pathophysiological interactions between obesity and heart. Conclusion: Conventional two‐dimensional Doppler echocardiography, integrated by relative new technological ultrasonic approaches, represents the reference technique to study and possibly clarify both the very complex hemodynamic changes induced by obesity and those relative to obesity treatment.